Novel extraction of bioactive compounds from algae using green solvent: Principles, Applications, and Future perspectives - Tan Phat Vo; Dinh Quan Nguyen; Thai Anh Thi Ho; Thuan Minh Nguyen; Nguyen Minh Huy Ha; Phong H.N. Vo (Journal of Agriculture and Food Research)
Bioactive compounds, such as phenolics, terpenoids, and fatty acids, are essential for pharmaceutical and health care applications; however, the extraction of these compounds from algae is challenging because of their low polarity and rigid cell walls. The applications of novel extraction techniques using green solvents have been widely researched because of the rising demand for sustainable production. This work aims to review novel extraction techniques, such as ultrasonic-assisted, microwave-assisted, enzymatic-assisted, and supercritical fluid extraction, using green solvents to recover bioactive compounds from algae. This review presents (i) the principles of using green solvent-based novel extraction techniques, (ii) the effect of extraction conditions on the overall yield of bioactive compounds, (iii) and the applications of green solvent-based extraction techniques in recovering bioactive compounds from algae. The metadata analysis is conducted to compare the extraction efficiency of those novel extraction techniques. Microwave-assisted extraction (MAE) shows the highest recovery efficiency (70 mg/g) in recovering the bioactive compounds among the four techniques. The data of novel extraction techniques will provide strong support for designing and practicing the extraction of bioactive compounds at an industrial scale. The review also proposes hybrid extraction techniques to improve the extraction yield of bioactive compounds. MAE can be combined with ultrasonic-assisted extraction, supercritical fluid extraction, and enzyme-assisted extraction, in which MAE acts as the pretreatment method.